2015
DOI: 10.1055/s-0034-1380415
|View full text |Cite
|
Sign up to set email alerts
|

Bis(indolyl)methane Alkaloids: Isolation, Bioactivity, and Syntheses

Abstract: Bis(indolyl)methane (BIM) alkaloids are an important group of bioactive natural products predominantly found in marine organisms. Thus, compounds like arsindoline A and B, vibrindole A, arundine, and trisindoline are found in marine bacteria, while the related compound, streptindole is obtained from Streptococcus faecium IB 37, found in human feces. In recent years, these molecules, which display a wide range of biological properties (antibacterial, antiviral, anti-oxidant, neurotoxic activity etc.), have attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…A mixture of compound 2 (252.15 mg, 1 mmol), 1-(3-(trifluoromethyl)phenyl)piperazine (535.2 mg, 1 mmol), and anhydrous K2CO3 (276 mg, 2 mmol) in MEK (10 mL) was heated at 80 o C for 16 h. After completion of the reaction with TLC control, the solvent was evaporated and the residue was purified by column chromatography using ethyl acetate/n-hexane (1:1) as the eluent to give pure product 16 [15]. White solid (300 mg, 75% isolated yield).…”
Section: Synthesis Of 1-(4-(4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)butyl)-1h-indole (16)mentioning
confidence: 99%
See 1 more Smart Citation
“…A mixture of compound 2 (252.15 mg, 1 mmol), 1-(3-(trifluoromethyl)phenyl)piperazine (535.2 mg, 1 mmol), and anhydrous K2CO3 (276 mg, 2 mmol) in MEK (10 mL) was heated at 80 o C for 16 h. After completion of the reaction with TLC control, the solvent was evaporated and the residue was purified by column chromatography using ethyl acetate/n-hexane (1:1) as the eluent to give pure product 16 [15]. White solid (300 mg, 75% isolated yield).…”
Section: Synthesis Of 1-(4-(4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)butyl)-1h-indole (16)mentioning
confidence: 99%
“…The most common method for the synthesis of BIMs involves consecutive nucleophilic addition of two molecules of indole (nucleophile) to an aldehyde (electrophile) as a one-pot reaction in the presence of a number of catalysts like BrĂžnsted, Lewis acids such as LiClO4, In(OTf)3, Dy(OTf)3, Sc(OTf)3, CAN, ZrOCl2, InCl3, heteropoly acids, ionic liquids, surfactants. [15][16][17] In our previous work, several UV-active bis(indolyl)methanes were prepared in the presence of 1,3dibromo-5,5-dimethylhydantoin (DBDMH) 18 and the UV-absorbing activity were investigated both in solution and polymer substrate. This study focuses on design and discovery of new bisindolylmethanes including arylpiperazine group.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that natural scaffolds containing either bis(indolyl)methane or benzimidazole core have been considered biologically relevant in the search of new potential applications as candidates with pharmaceutical activity. [1][2][3][4][5] Even though indole-3-carbinol 1 and their metabolic products such as 3,3ÂŽ-diindolylmethane (DIM) 2 and the oligomers 3-4 have shown renewed anticancer properties; 6,7 another naturally occurring indole alkaloids featuring a central azaheterocyclic core decorated with either 1H-indol-3-yl or bis(1H-indol-3-yl)methane moieties have gained a prominent position as promising cytotoxic, antifungal and antibiotic agents with innovative mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…23 Studies revealed that streptindole exhibited DNA-damaging and genotoxic properties. 24 We have been committed to the development of new antiviral candidates based on indole natural products for a long time. Streptindole with a simple structure has aroused our great interest.…”
Section: ■ Introductionmentioning
confidence: 99%